A Systematic Analysis of Innovation Studies: A Proposed Framework on Relatioship Between Innovation Process and Firm's Performance - Zainal Abidin, Suriati Binti; Mokhtar, Sany Sanuri Bin; Yusoff, Rushami Zien Bin (School of Business and Management Institut Teknologi Bandung, 2011)
Innovation has been discussed in a broad field. Scholars have defined and discussed innovation in various forms and perspectives. Whether empirical or conceptual, the discussions have delineated innovation in various perspectives such as organizational innovation, newness, innovation management, innovation as interactive model and types of innovation. In fact, due to the competitive environment, innovation is crucial and has become a niche for firm’s performance. This paper aims to provide a systematic analysis and propose framework that emphasizes on investigating the relationship between innovation and firm performance. Based on literature review, this paper proposes six constructs which can be used to examine the innovation implementation at firm level. The constructs are leadership, managerial levers, business processes, innovation process, innovation outcome and firm performance. Keywords: innovation, innovation outcomes, firm performance